Dr. Michelle Sieffert — Deep Plane Facelift — Columbus - Sieffert, Michelle (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Michelle Sieffert, practicing in Columbus, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003315; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; columbus